The Dual Use of Civilian and Military Technologies in the Battlefield of the Future - Mazal, Jan (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
This chapter discusses the reasons for and outcomes of the inevitable and dynamic transition to a highly technological future battlefield that will dramatically affect all armies worldwide. Military technology and progress motivation are specific and backed by long-term incremental development, leading to the achievement of pragmatic goals, which are deeply coded in the human genome and are similar for some military and civilian domains, such as battlefields and businesses. This chapter presents fundamental evidence that leads to a better understanding of particular aspects of modern warfare and the technological nature of future conflicts. It discusses the complex relationship between cutting-edge military technology and dual-use aspects and explores the ethical implications and potential future trajectories of such interconnected technological developments. Keywords: Future Battlefield, Dual-use aspects, Technological Warfare